Inheritance Rights of Stepchildren in the Perspective of Compilation of Islamic Law - Wati, Erna; Rettina, Tiara (Faculty of Sharia, IAIN Metro, 2022)
The presence of a stepchild in a marriage requires a certainty of legal rights for inheritance and bequest division given by parents because of the difference status of stepchild with biological children, the purpose of this journal is to determine the rights of a stepchild in the division of inheritance and bequest division that can be obtained from their parents, especially in terms of the islamic law of inheritance. Method used is normative law research by approaching to reviewing and analyzing the law and positive regulations. The conclusion of this journal is that stepchild is not an heir in the family but reserves the right to inherit by way of will or bequest.